Fraction L17 of Lachesis muta muta venom promotes the cellular proliferation in vitro and accelerates the wound healing in mice - Ruiz-Garcia, Estefanny (2017)
Lachesis muta muta is a Viperid snake distributed throughout South America and its bite has been reported to cause hypotension, bradycardia, vomiting, diarrhea and affects the coagulation cascade. Studies have shown that proteins isolated from the L. m. muta venom have pharmacological activity against carcinogenic cell lines, coagulation disorders and hypertension control. The present work reported the proliferating activity in vitro and in vivo of the fraction 17 of L. m. muta (L17) on the wound healing. We tested the activity of L 17 at different concentrations in 3T3 fibroblasts and HaCaT Keratinocytes, as well as their activity on the healing process in Swiss-Webster mice. L17 did not affect the survival of fibroblasts and keratinocytes in cell culture and further with 10 μg/ml promoted the proliferation of keratinocytes after 72 h of treatment. In vivo experiment, L17 accelerated the healing process, increasing the cellularity at day 8, and the blood vessel production at day 4 and 8. Likewise, it stimulated the deposition of type I and type III collagen and favored the activity of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) as well as the reduction of the markers of oxidative stress malondialdehyde (MDA) and carbonyl protein (CP). The results suggest that L 17 could be effective in the healing treatment, since it favors the cellularity and the angiogenesis; in addition, it promotes the deposition of collagen for the formation of Extra Cellular Matrix (ECM). L17 possibly has a proliferative and protective effect against oxidative stress in the wound healing, been a prospective treatment.